The adoption of intensive monocrop horticulture in southern Cameroon - Gockowski, J.; Ndoumbe, M. (Elsevier, 2004)
Results from a 1997 survey of 208 households in the humid forest zone of southern Cameroon indicate that African policy makers seeking to intensify agricultural production should focus attention on the horticultural sub-sector. The survey, which gathered information on horticultural production practices, found that the average expenditure on agro-chemical inputs by horticultural producers using monocrop production systems was 190 US$/ha, which greatly exceeds the FAO reported national average expenditure of 6.50 US$/ha. A logit model of monocrop adoption indicated that the size of land holding per household had a negative effect on adoption, congruent with population-driven technical change and that increases in unit transportation costs significantly decreased the probability of adoption. These findings suggest that policy makers should target horticultural intensification in areas of higher population density and promote investment in rural roads. The age of the household head had a significant negative and elastic effect on adoption, which in combination with an increase in the cohort of younger farmers in the rural population induced by macro-economic events contributed to the spread of intensified horticulture. In the study area, roughly two-thirds of rural households also produce cocoa and the quantity of cocoa produced was positively associated with adoption of intensive horticultural systems suggesting that export crop promotion indirectly facilitated diversification of agriculture. Women’s participation in intensive monocrop production was limited and efforts to promote their greater involvement are recommended.